2017
DOI: 10.1080/19648189.2017.1375997
|View full text |Cite
|
Sign up to set email alerts
|

Sources of uncertainties for total chloride profile measurements in concrete: quantization and impact on probability assessment of corrosion initiation

Abstract: Reliability methods have proved in the past that they were rational aid-tools for the safety assessment of existing structures, within which some uncertainties occurred. Condition assessment is usually carried out using on-site measurements, which are assumed perfect. However, it is now accepted that some significant uncertainties may affect the assessment of material properties using semi-destructive methods. The purpose of this paper is to present a method for the identification and evaluation of measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…It should also be noted that the standard deviation values are higher and more variable on the sheltered side ( Fig. 5a) and that they remain lower than 0.000156, the upper bound of the standard deviation of the error on chloride measurements calculated by Bonnet et al (2017). Moreover, the lower the chloride content, the smaller the standard deviation.…”
Section: Chloride Profilesmentioning
confidence: 83%
See 1 more Smart Citation
“…It should also be noted that the standard deviation values are higher and more variable on the sheltered side ( Fig. 5a) and that they remain lower than 0.000156, the upper bound of the standard deviation of the error on chloride measurements calculated by Bonnet et al (2017). Moreover, the lower the chloride content, the smaller the standard deviation.…”
Section: Chloride Profilesmentioning
confidence: 83%
“…Recent studies have highlighted the spatial variability of chloride-induced reinforced concrete corrosion with an impact on infrastructure network maintenance optimization (O'Connor and Kenshel, 2013). In the following, the focus is on total chloride content because, firstly, measurement methodology is not subject to debate (Bonnet et al, 2017) and, secondly, because it is the key parameter for already available maintenance optimisation methods.…”
Section: Introductionmentioning
confidence: 99%
“…The vertical error bars for the destructive methods are based on a recent study by Bonnet et. al [59] where the vertical standard deviation for total chloride content is approximately equal to 6% (calculated from 42 measurements). Unfortunately, no studies are found about the sources of uncertainties for the free chloride profile measurements in concrete by destructive method.…”
Section: Comparing Chloride Profiles Obtained By Resistivity To Thosementioning
confidence: 97%
“…Unfortunately, no studies are found about the sources of uncertainties for the free chloride profile measurements in concrete by destructive method. However, as explained in [59], the protocol for obtaining the total and free chloride profiles are similar. In general, and considering the horizontal error bars, the destructive profiles lie in the range of the non-destructive profiles.…”
Section: Comparing Chloride Profiles Obtained By Resistivity To Thosementioning
confidence: 99%
“…When considering destructive methods, such as the Volhard method, errors in measurement depend mainly on different steps of the protocol, such as grinding, preparation of powder, acid attack, dilution, and concentration measurements. Bonnet et al [57] analyzed 42 chloride content measurements in order to assess the total measurement error by considering three main errors (protocol error, sample error, and human error). The probability of the detection of corrosion initiation was expressed as a function of the margin between the critical concentration and the real concentration, i.e., C(t) − C crit .…”
Section: Measuring Techniquesmentioning
confidence: 99%